PENGARUH PENERAPAN INTERNATIONAL FINANCIAL REPORTING STANDARD TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Aprilia, Renita; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study aims to examine empirically the effect of adoption of IFRS, Quality Auditor, Company Size andSolvency against Timeliness Submission of Financial Reports on Consumer Goods company in the year 2012 to2015. This type of research is quantitative. The population in the study are all Consumer Goods company listedon the Indonesia Stock Exchange and give a financial report for the period 2012-2015 of the 36 companies, with asampling technique used jenuh sampling. Data were analyzed using multiple linear regression. Based on theresults of hypothesis testing can be concluded that variable; 1) Application of IFRS significant effect onTimeliness of submission of Financial Statements on Consumer Goods company in the year 2012 to 2015.Companies that have implemented IFRS disclosures are required to perform extensive, 2) Quality Auditorsignificantly influence the accuracy of time Submission of Financial Reports on Consumer Goods company inthe year 2012 to 2015. KAP large (affiliated with the International KAP) has isentif more powerful and havemore human resources to complete the audit work a lot faster to maintain its reputation them.3) company sizesignificantly influence the companys submission of Financial Statements Consumer Goods in 2012 -2015, Thelarger the company, the better the control system owned 4) Solvency significantly influence the accuracy of timeSubmission of Financial Reports on Consumer Goods company in the year 2012 to 2015. The high amount ofdebt the company will lead the audit process is relatively long due to the increase for auditor in the processaudting.Words key: IFRS, Quality Auditor, Company Size, Solvency, Timeliness of submission of Financial Statements